Creating Shared Values: A Case Study of Samudera Indonesia and Soedarpo Family - Rildo, Rizki Dwianda; Zwespana, Anastasya; Oktafira, Ariela; Nugraha, Fathur Bhakti; Narendra, Gita; Indrajaya, Amelia Naim (Journal of Sustainable Community Development (JSCD), 2024)
PT Samudera Indonesia Tbk (SMDR) is one of the biggest logistic and shipping companies in Indonesia, it is majority-owned by one of the oldest family businesses, the Soedarpo Family. This research aims to describe the ESGRC activities at SMDR. Based on our interview and study literature, the result shows SMDR has excellently implemented both ESG and GRC. SMDR believes in going beyond its mission of providing quality marine cargo transportation and logistics services, to create shared value for its stakeholders. For SMDR, to be responsible for the business is not only through Corporate Social Responsibility (CSR) activities, but also to ensure that every business operation conducted has complied with environmental and social regulations.